Renard. Histoire burlesque chantée et jouée - Stravinsky, Igor 1882-1971; Boulez, Pierre 1925-2016; Ramuz, Charles-Ferdinand 1878-1947; Le Domaine musical (Paris, France) (Paris Disques Adès, 1969)
'Impact de la musique contemporaine' was a series of lavishly designed 7" records under Gilbert Amy's direction of Le Domaine musical, a society founded by Pierre Boulez, Hermann Scherchen, and Jean-Louis Barrault.
Perforated record cover. Portrait of Stravinsky on the record label.
Keywords: 20th Century (1901-2000); Music theater; Avant-garde